Hubungan antara Aspirasi Siswa dan Dukungan Orangtua dengan Motivasi Belajar serta Implikasinya terhadap Bimbingan Konseling - Wati, Elmira; Daharnis, Daharnis; Syahniar, Syahniar (Konselor, 2013)
There are some factors that become constraints of successful learning for students in SMA Negeri 1 Singingi Hilir namely; lack of spirit in learning, lack of concentration span, high frequency in asking permission, or unreturn after asking permission as well as unfulfilled the assignment. In short, the factors are estuaried to students’ low motivation issue. Learning motivation can be effected by stundents’ aspiration and parents’ support. This study is aimed at obtaining empirical data related to: students’ aspiration in SMA Negeri 1 Singingi Hilir, parents’ support in SMA Negeri 1 Singingi Hilir, learning motivation, correlation of students’ aspiration and parents’ support with learning motivation in SMA Negeri 1 Singingi Hilir. This study  belongs to descriptive and correlational research. Descriptive analysis and linear reggretion analysis are used in analyzing the data. The result of the study shows that students’ aspiration in SMA Negeri 1 Singingi Hilir  is classified medium, parents’ support in SMA Negeri 1 Singingi Hilir is classifed high, students’ learning motivation in SMA Negeri 1 Singingi Hilir is classified medium, students’ aspiration and parents’ support give significant correlation with learning motivation. It is higly suggested that counsellor created Guidance and Councelling program related to students’ aspiration in  career information services and career oriented services, parents’ support in form of home visit and regular parents’ school visit, learning motivation in form of learning information center, content mastery services and personal guindance and councelling  services, next prospective researchers that it is expected to conduct more advance and comprehensive reseach by using other variables that influence learning motivation.